Welfare of the child as the paramount consideration in custody cases: a comparative study of civil and Islamic laws in Malay - Abd Malek, Normi (Current Law Journal, 2013)

(untitled)
In general, both civil and Islamic laws are in agreement; that the welfare or interests of the child are the paramount consideration in deciding disputes relating to custody. Factors such as physical and emotional well-being, age, wishes of both the children and parents, preservation of status quo, conduct of the parties and religion are among the factors that will be taken into consideration in determining the interests of the child. However, in details, the laws might give different emphasis to the different factors which determine the interests of the child. This paper attempts to discover to what extent civil and Islamic laws are similar and to what extent they differ in considering the above factors. The reason behind the differences will be highlighted